Study structural, dielectric and ferroelectric properties of Pb (Zr1-x Tix)O3 ceramics near the morphotropic phase boundary - Abdulsamee Fawzi Abdul Aziz AL-Bayati (Tikrit Journal of Pure Science, 2023)
In the present work, Pb(Zr(1-x)Tix) ceramics (x = 0.50, 0.48, 0.45 and 0.42) were prepared using the solid state reaction method, at the sintaring temperature (1100 oC ) for (6hr).X-ray diffraction results demonstrate that all the samples lie within the morphtropic phase boundary (MPB) region in the pure perovskite tetragonal structure with Miller transactions (100), (110), (111), (200), (210), (211), (220), (103) and (311) that the prevailing trend is (110) and the results of plasticity microwave very close sense of distance intra-convergent also relatively few crystalline defects. Increasing the bulk density of the true density of altered concentration of zirconium and titanium. Results of the examination microscope also showed that the particle size (Dnm) be tight between the samples and the homogeneity of the granules, as well as increasing the homogeneity of compositional structure, causing an improvement in the structural and electrical properties. Shown technique results EDAX compound of the interacting elements of the composition and there is little difference between the real weight and the weight is noticeable. The temperature and concentration of titanium dependences of the dielectric constant of the ceramics has been investigated in detail. Excellent dielectric properties have been obtained for the selected compositions. Polarization-Elctric field hysteresis studies were carried out for all compositions at room temperature. It was found that with the increase of concentration of titanium content in the composition the remnant polarization decreases and ferroelectric loops get constricted.